Analysis of The Relationship Coincident Economic, A Leading Economics and Regional Index Againts The Jakarta Islamic Index - Mita Agustiani; Kusnendi Kusnendi; Neni Sri Wulandari (Universitas Pendidikan Indonesia, 2020)
The Islamic Sharia capital market has a literacy rate and very low inclusion, and one instrument has to fluctuate every development at IE Jakarta Islamic Index (JII). It is becoming a language interesting given Sharia Capital Market have an important role because of the biggest contributor for the assets into the Islamic finance industry Indonesia. Thus, this research aims to find out how the influence of economic indicators. Leading Economic Indicator (LEI) composed of Customer Price Index (CPI) and the value of the exchange rate, the Coincident Economic Indicators (CEI) consisting of Retail Sales and money supply (M2), and the last Regional Index where authors take first stock index in the world, i.e., Index Dow Jones Islamic market and index the Dow Jones Industrial Average with the Jakarta Islamic Index. This research analyses Vector Error Correction Models (VECM) and secondary data for 60 periods from January 2014 to December 2018. This study showed that Retail Sales, the Dow Jones Islamic market, and the Dow Jones Industrial Average Index did not affect, Money supply (M2) and a negative exchange rate effect. In contrast, the Customer Price Index (CPI) had a positive effect. The macroeconomic variables will affect the implications of this research, namely the development of the Jakarta Islamic Index (JII) price. The money supply (M2), Customer Price Index (CPI), and the exchange rate become variable, which has a big influence. In contrast, the Retail Sales, the Dow Jones Islamic Market (DJIM), the Dow Jones Industrial Average (DJIA) has influence but are not so strong. Therefore, the stability condition of the macroeconomy is stable, so the share price development of the Jakarta Islamic Index (JII) is stable and moving up.